Application of metabolic phase-specific modified nutrition risk in critically ill score: a prospective observational study in critically ill patients - Lee, Geon Ho; Kim, Ye Ju; Park, So Hyang; Park, Sunny; Lim, Sung Yoon; Choi, Soo An (Frontiers in Nutrition, 2024)
Background & aims: The prevalence of malnutrition in intensive care units (ICU) is high and can be caused by poor intake or absorption of nutrients in the digestive trackassimilation, as well as diseaserelated inflammation. As strong catabolism restricts nutrient supply and potentially leads to subsequent malnutrition, appropriate nutrition should be provided based on the metabolic status. However, nutritional support strategies for considering the metabolic phase are not well established. Therefore, this study aimed to establish a strategy for nutritional support in each phase by implementing a phase-specific modified Nutrition Risk in Critically Ill (mNUTRIC) score.